Documents pour l'étude de la religion et de l'organisation sociale des Sherpa - Saṅs-rgyas-bstan-ʼdzin, Gser Dgon, 1924-1990; Macdonald, Alexander W. ([s.n.], 1971)
On the history of the Lamaist religion and social organization of the Sherpa people of Solukhumbu, eastern Nepal.